The Influence of Values on E-learning Adoption. (November 2019) - Mehta, Ashwin; Morris, Neil P.; Swinnerton, Bronwen; Homer, Matt
Abstract: As technology continues to pervade our lives, the influence of culture on technology adoption is of significant interest to researchers. However, culture, as a group-level construct may not give meaningful results when related to individual-level adoption. Although culture has been integrated into technology adoption models, values are the individual-level representation of culture, and are more appropriate to include in technology adoption models. There have been few studies attempting to explore the influence of values on adoption models, and none within the sphere of digital education. The purpose of this exploratory study is to integrate values with technology adoption models and apply the novel conceptual model to the context of digital education. In this study we investigate the influence of individual-level values on the adoption of e-learning by workers in The Gambia and the UK. Using the Unified Theory of the Acceptance and Use of Technology (UTAUT2) as a base model, we integrate values relating to conservation of the status quo and self-enhancement from Schwartz's Theory of Human Values. Taking this approach, we develop and introduce the Values-Enhanced Technology Adoption (VETA) model. We tested the VETA model on the adoption of e-learning by workers in The Gambia and the UK. Empirical results demonstrated the influence of self-enhancement values in the model via social influence, price value and performance expectancy. The UTAUT2 base model was partially validated in that performance expectancy, price value and habit primarily influenced worker intention to use e-learning. We conclude that VETA will be a useful model to researchers studying technology adoption. Highlights: We develop and validate the Values-Enhanced Technology Adoption (VETA) model. We empirically demonstrate that the model partially applies to e-learning adoption in both The Gambia and the UK. We partially validate the UTAUT2 model in The Gambia. We show that the value of achievement indirectly influenced learner intention to use e-learning via adoption factors.